A theory framework for balancing vertical and horizontal leadership in projects. Issue 1 (January 2018) - Müller, Ralf; Sankaran, Shankar; Drouin, Nathalie; Vaagaasar, Anne-Live; Bekker, Michiel C.; Jain, Karuna
Abstract: This paper develops a framework for understanding the interaction between person-centered leadership by project managers (a.k.a. vertical leadership (VLS)) and team-centered leadership by individuals in the project team (a.k.a. horizontal leadership (HSL)). It builds on Archer's Realist Social Theory and its morphogenetic cycle, which describes the interaction of structure with agency for task fulfillment and the resulting reshaping (morphogenesis) or continuation (morphostasis) of structure for subsequent iterations of the cycle. Data were collected globally in 33 case studies with 166 interviews and analyzed using Alvesson's Constructing Mystery technique. A theory about the cycles and events that shape the interaction between VLS and HLS is developed, which includes events such as nomination, identification, selection, execution and governance, as well as transitioning. Managerial and theoretical implications are discussed. Highlights: A theoretical framework for the interaction between vertical and horizontal leadership in projects. Builds on the Archer's morphogenetic cycle to model structure and agency for project leadership. Identifies the recursive cycles of nomination, identification, selection, execution & governance, and transitioning. Empirical evidence from 166 interviews and a range of industries.